Rancang Bangun Sistem Informasi Penggajian Dan Kas Kecil Menggunakan Metode Rapid Application Development - Anisa Maulida; Alin Lestari; Robby Alvian Jaya Mulia; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Every company in this global era uses existing technology to make it easier to obtain correct (accurate) and actual data in line with advances in civilization and technological developments that make it easier for humans to obtain information (according to current conditions). Information is essential for planning and control when developing strategies to meet company goals. It is very important that a company or business make changes to digital systems. However, some companies or businesses continue to use a payroll and petty cash management system that only relies on calculations that have not been integrated with the database. PT. Sindang Multi Ekatama is a company engaged in the distribution of consumer goods. As a company that continues to grow, PT. Sindang Multi Ekatama requires an information system that is integrated with the database so that it can assist in managing payroll and petty cash so that it is more efficient and well organized. Therefore, this research will be conducted to analyze and design a payroll and petty cash information system using the Rapid Application Development method at PT. Sindang Multi Ekatama, using the Laravel 10 framework and MySQL 5.7 database. With an information system that is integrated with the database, managing payroll and petty cash at PT. Sindang Multi Ekatama could be more organized and efficient. In addition, this information system can also reduce the risk of salary calculation errors, inaccurate petty cash management, and the difficulty of controlling company expenses.